Determinants of Livelihood Outcome Among Rural Households in Ondo State Forest Reserves - Nigeria - Olawale Julius Aluko; Ayodotun Bobadoye; Olajumoke Celinah Odeyale (Bina Nusantara University, 2026)
The study examined the determinants of livelihood outcomes among rural households residing in forest reserves in Ondo State, Nigeria. Socio-economic characteristics, the livelihood outcomes and relationship to household well-being, as well as the effect of access to the land on livelihood performance were critically assessed in this study. A total of 216 respondents were selected from mangrove/freshwater swamp ecological zone forests of the state using multistage sampling techniques. A structured questionnaire, focus group discussion, and interviews of key informants were used to gather data, which were analyzed using descriptive and inferential statistics. The result revealed the respondents' mean age to be 43.2 years, the household size to be approximately 6, and a mean annual income of ₦312,400. The livelihood outcome index of the respondents came out with a mean lower than expected value, representing a very low livelihood outcome despite the overreliance on the forest resources. Due to the nature of the zone, the food availability recorded a high mean index of 63.5%, while other indicators used to operationalize food security recorded a low mean index. The regression result revealed that some of the socio-characteristics, such as level of education, income, age, primary occupation, and indigenous status, have positive implications on livelihood outcomes of the respondents in the study area. By implication, the study concluded that the livelihood outcome generally depended on socio-economic abilities, and availability of resources alone does not guarantee food security. Therefore, improving households’ well-being is a function of numerous factors in the study area.